A Study on Effects of Magnesium Sulphate Infusion in Preventing Cardiac Arrhythmia During Off Pump Beating Heart Coronary Artery Bypass Grafting (CABG) Surgery (Ibrahim Cardiac Medical Journal, 2019)
Objective: The objective of the present study was to see the effect of magnesium in preventing cardiac arrhythmias in patients undergoing coronary artery bypass grafting (CABG) surgery.Methods: This study was carried out in the Department of Anesthesia, Analgesia and Intensive Care Medicine (Cardiac Anesthesia Wing) of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka who underwent CABG surgery under general anaesthesia. A total of 60 patients scheduled for CABG were consecutively selected and were randomly divided into study group and control group. Patients aged 35-70 years irrespective of sex, ASA grade I & II, NYHA functional class I & II and ejection fraction 35-65% were included in the study. The study group was treated by vecuronium, fentanyl and magnesium sulphate infusion, while the control group was treated by vecuronium and fentanyl infusion. The demographic variables, preoperative clinical characteristics, peroperative variables and haemodynamic findings were observed at different time intervals.Results: The mean ages of the study and control groups were 51.0 ± 6.9 years and 53.8 ± 6.2 years respectively. Males demonstrated their predominance in both magnesium (83.3%) and control (76.7%) groups. The distribution of preoperative confounding factors like diabetes, previous MI, hypertension and ejection fraction were not statistically different between the study groups. Two-thirds (67.7%) of the patients in magnesium group and 53.3% in the control group required 3 grafts. Number of 4 grafts in magnesium and control groups was 20% and 30% respectively and that of 2 grafts was 13.3% and 16.7% respectively. In the study group, out of 30 patients, 3(10%) developed arrhythmia, while in the control group out of 30 patients, 5(16.7%) developed arrhythmia (p = 0.353).The haemodynamic parameters in patients receiving magnesium were more stable during the whole period of observation.Conclusion: The findings of the study suggest that magnesium could reduce the development of arrhythmia to an acceptable level in patients undergoing beating heart CABG surgery. However, further study with large sample is recommended to achieve a conclusive remark.Ibrahim Card Med J 2017; 7 (1&2): 37-43